Ecology and conservation of restricted reptiles - Petford, Melissa (My University, 2019)
Across the globe, reptile species are threatened by anthropogenic activities, including habitat destruction, habitat degradation, expanding human settlements and climate change. Those with restricted ranges are often the most vulnerable due to their limited dispersal capabilities, narrow thermal tolerances and specific habitat requirements. Many of these restricted species are also poorly understood, with a lack of knowledge concerning their ecological and physiological requirements. In order to design effective conservation strategies for these restricted species, these knowledge gaps need to be filled. The aim of this thesis was to gain a deeper understanding on the biology of some of the endemic and restricted reptiles in the Soutpansberg Mountains. This mountain range is located in the Limpopo Province of South Africa and is a unique study area due to its sub-tropical location, habitat heterogeneity and the fact that it is located in the replacement transition zones of three biogeographic subregions. This has led to the mountains supporting extremely high faunal and floral biodiversity and endemism, reptiles being no exception. However, to date there have been few ecological studies into the reptile fauna of the area and the ecological requirements of many of these species are unknown. There are several threats that species from the mountains currently face including habitat destruction, agriculture, silviculture, mining and climate change. This thesis is made up of four main parts: firstly, I investigated the broad scale distribution patterns, climatic requirements and potential interspecific interactions of five of the rupicolous, endemics using ecological niche modelling (Afroedura pienaari; Lygodactylus incognitus: L. soutpansbergensis; Platysaurus relictus and Vhembelacerta rupicola). Results indicated that most species were limited by climatic factors, with the average temperature of the coolest three months having the most influence on the majority of the species, suggesting that they may be negatively affected by climate change in the future. Interspecific interactions between these species are not likely to affect broad-scale distribution patterns. Secondly, I examined the microhabitat requirements and potential niche separation of two, endemic Lygodactylus geckos: L. incognitus and L. soutpansbergensis by recording fine- and broad-scale habitat variables. Results indicated that the two species showed differences in their microhabitat selection, but that interspecific aggression was unlikely to be the factor causing these differences. Instead, their morphology and physiology were likely driving microhabitat selection. This study revealed microhabitat requirements of the two species, knowledge of which is important for future conservation efforts in the area. Next, I investigated the daily activity patterns of the two Lygodactylus geckos by conducting scan surveys along transects in the mountains. Results showed that L. incognitus was more active in cooler temperatures whilst L. soutpansbergensis was more active in warmer conditions. These results suggest that L. incognitus may be more vulnerable than L. soutpansbergensis to the effects of climate change and that physiological studies are required to investigate adaptive capability. Finally, I explored the potential effects climate change will have on the distribution of eleven rupicolous reptiles using ecological niche modelling. These species are likely to have limited dispersal abilities and thus are unlikely to be able to track suitable conditions in the face of climate change; therefore, I also identified potential climatic refugia. Results indicated that four species in particular are likely to be extremely vulnerable to the effects of climate change with large reductions in suitable habitat between current and future projections. The western Soutpansberg may act as a climatic refugia in the future. I recommended that detailed investigations into the physiological requirements of these vulnerable species be performed in order to develop models that are more accurate. Long-term monitoring projects in the mountain should also be executed in order to track these potential range reductions. Ultimately, this thesis resulted in the gain of valuable ecological information on several restricted reptiles of South Africa for which there was previously few data. This information is vital for ongoing conservation assessments and planning in the region. One of the main findings of this thesis is that ongoing anthropogenic pressures will likely have negative effects for the majority of the species studied here.
A Thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, South Africa May 2019